Recent Advances in the Synthesis of Dialkyl (Aryl) α-(Aryl/Heterocyclic/Heteroaryl- α-(Aryl/Heteroarylamino)Phosphonates - Ali, Tarik E.; Assiri, Mohammed A.; Hussien, Mohamed; El-Tantawy El Sayed, Ibrahim (Current Organic Chemistry, 2023)
This review describes recent advances that are commonly applied in the synthesis of dialkyl (aryl) α-aminophosphonates containing heterocyclic compounds. The target structures are divided into three categories, which include α-aminophosphonic acids and their diesters bearing a heterocyclic or heteroaryl system at the α-carbon, nitrogen atom, or both. The synthetic protocols based on the Kabachnik-Fields and Pudovik reactions as the main pathways for the construction of these features, besides other miscellaneous methods. This review may be a useful resource for researchers and it will help them to work in this emerging research area.
Keywords: α-aminophosphonate